2018
DOI: 10.1007/s10680-018-9481-5
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Segregation Patterns in Belgium, Denmark, the Netherlands and Sweden: Neighbourhood Concentration and Representation of Non-European Migrants

Abstract: In this paper, we use geo-coded, individual-level register data on four European countries to compute comparative measures of segregation that are independent of existing geographical sub-divisions. The focus is on non-European migrants, for whom aggregates of egocentric neighbourhoods (with different population counts) are used to assess small-scale, medium-scale, and large-scale segregation patterns. At the smallest scale level, corresponding to neighbourhoods with 200 persons, patterns of over- and under-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 34 publications
2
49
1
Order By: Relevance
“…The data used here are based on population register data for the entire Norwegian population registered as resident on 1 January 2011, provided by Statistics Norway. The results are compared to corresponding figures from Sweden, Denmark, the Netherlands and Belgium, as described in Andersson et al (2018). To facilitate comparative analyses, we have aimed to make the data as similar as possible across countries.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data used here are based on population register data for the entire Norwegian population registered as resident on 1 January 2011, provided by Statistics Norway. The results are compared to corresponding figures from Sweden, Denmark, the Netherlands and Belgium, as described in Andersson et al (2018). To facilitate comparative analyses, we have aimed to make the data as similar as possible across countries.…”
Section: Methodsmentioning
confidence: 99%
“…Our measure of the representation of non-European immigrants is calculated from the percentile distribution of the concentration of non-European immigrants in a fashion identical to that in Andersson et al (2018). Thus, non-Europeans are overrepresented in a percentile bin if the value is above 1, and under-represented if the value is below 1 (Andersson et al 2017(Andersson et al , 2018Hennerdal and Nielsen 2017).…”
Section: Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that neighbourhood effects are stronger at spatial scales that are much smaller than administrative units. A recent study by Andersson et al (), also using the k‐nearest neighbour approach, showed variation in ethnic concentrations across different spatial scales.…”
Section: Literaturementioning
confidence: 99%
“…Nevertheless, recent studies in Belgium have found extensive ethnic residential segregation. Andersson et al (2017; see also Costa & De Valk, 2018) calculated the segregation of non-EU foreigners and found that close to 50% of all non-EU foreigners in Belgium would have to move to completely desegregate Belgium. Verhaeghe, Van der Bracht, and Van de Putte (2012) confirm these findings for Turkish, Maghreb, and Eastern and Central European minorities in Ghent, but they also note that segregation is declining in Ghent and Antwerp.…”
Section: Introductionmentioning
confidence: 99%